Perception of the Implementation of Blockchain Technology in Portuguese Supply Chains - Pereira, P. A.; Martins, A.; Ferreira, J. (Euroma 2022 Conference, 2022)
This paper investigates the perception of implementation of Blockchain Technology (BCT) in the Supply Chain Management from Portuguese organizations. The research intends to analyse the homogeneity through the scenario of adoption and different positions in the supply chain regarding familiarity, expected impact and its association with the difficulty and disposition to adopt. The literature review identified the main properties that were used to formulate a structured survey applied to managers from food, transportation, and pharmaceutical sectors. Data gathered from 48 organizations, analysed through SPSS version 27.0 revealed that exists moderate associations between constructs and that organizations have similar behaviours.